2014
DOI: 10.1542/hpeds.2013-0078
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors Associated With Bronchiolitis Readmission

Abstract: Overall, 6.4% of hospitalized patients with bronchiolitis were readmitted. Our data did not identify any inpatient medical management or modifiable risk factor associated with readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
0
9
0
7
Order By: Relevance
“…The present study' s 30-day FTT-specific readmission rate (4.8%) is comparable to those found in other pediatric-specific conditions such as pneumonia (3.1%), bronchiolitis (6.4%), and diabetic ketoacidosis (2.5%). [19][20][21] The 3-year and 30day all-cause readmission rates (39.5% and 14.5%, respectively) are not unexpected given that malnutrition has been shown to be associated with increases in hospitalization rates, LOS, and mortality. [22][23][24] In addition, nearly one-half of our cohort included children with a CCC, a group known to have an elevated risk for 30-day all-cause readmission (25.4%) 15 over that of the general pediatric population (6.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study' s 30-day FTT-specific readmission rate (4.8%) is comparable to those found in other pediatric-specific conditions such as pneumonia (3.1%), bronchiolitis (6.4%), and diabetic ketoacidosis (2.5%). [19][20][21] The 3-year and 30day all-cause readmission rates (39.5% and 14.5%, respectively) are not unexpected given that malnutrition has been shown to be associated with increases in hospitalization rates, LOS, and mortality. [22][23][24] In addition, nearly one-half of our cohort included children with a CCC, a group known to have an elevated risk for 30-day all-cause readmission (25.4%) 15 over that of the general pediatric population (6.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is evidence that HHI is a risk factor for readmission for other but not all conditions. 20,21,29 Although socioeconomic status may not be associated with FTT on a population level, previous evidence has shown that food insecurity (a marker of poverty) is associated with poorer health outcomes, possibly explaining the relationship between low HHI and FTT readmission. 30,31 Second, for patients with more permanent feeding modalities such as G/J tubes, this study found a reduced risk for readmission compared with temporary modalities such as NG/NJ tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the factors related to readmission in the literature include respiratory syncytial virus/rhinovirus coinfection, 8 age under 2 months, male sex, 9 lower gestational age, chronic lung disease, living with school-age siblings, 10 living <20 miles from hospital, low income, 5 and being in the progressing stage of illness. 6 None of these, however, are preventable factors.…”
Section: Introductionmentioning
confidence: 99%
“…En la bronquiolitis factores como el sexo no parecen influir sobre una posible re-hospitalización(263;264).Por lo que respecta a la edad se aprecia una discreta protección frente al reingreso cifrada en un 1% por cada mes de vida. En general, para la bronquiolitis, a menor edad mayor posibilidad de reingreso(263).Aquellos pacientes que son trasladados a otros centro sanitarios durante su primer ingreso, tienen un mayor riesgo de readmisión que los que son dados de alta al domicilio (2,4 veces). La mayor gravedad del episodio medida en cuanto a días de hospitalización, ingreso en UCIP, necesidad de medicación, traslado entre centros, supone, lógicamente, un factor de riesgo para nuevos ingresos(265).En nuestro análisis, la hospitalización en hospitales de 2º o 3 er nivel supone menor probabilidad de reingreso, en patología respiratoria, que si ésta se produce en hospitales comarcales.…”
unclassified
“…En cambio, en el estudio de Riese sobre bronquiolitis, donde analiza factores demográficos asociados con el reingreso, se observa una relación entre la distancia al centro hospitalario y extensión del área que cubre con la readmisión. Pacientes que viven próximos a hospitales que abarcan áreas geográficas extensas tienen más riesgo de volver a internar(263).En nuestro estudio el uso de antibióticos por vía sistémica protege de la posibilidad de reingreso. Como es sabido, la bronquiolitis es una patología de causa vírica en la que el uso de antibióticos no está indicado, salvo en el caso de sospecha de sobreinfección bacteriana.…”
unclassified